Inhibition effect of AGEs formation in vitro by the two novel peptides EDYGA and DLLCIC derived from Pelodiscus sinensis - Chen, Nuo; Wang, Nan; Fang, Qiaoyun; Yu, Zuolong; Hu, Yiyuan; Jin, Jiancang; Yang, Shengli (Frontiers in Nutrition, 2025)
The antioxidant activity of natural products is closely related to their antiglycation effects. This study aimed to examine the antiglycation activity and elucidate the underlying mechanisms of two specific peptides, EDYGA (Glu-Asp-Tyr-Gly-Ala) and DLLCIC (Asp-Leu-Leu-Cys-Ile-Val), derived from protein hydrolysates of the Pelodiscus sinensis. Both EDYGA and DLLCIC were efficient in bovine serum albumin (BSA)/glucose model to inhibit BSA glycation, while DLLCIC showed higher antiglycation activity than EDYGA. Firstly, it was found that EDYGA and DLLCIC could inhibit the formation of NEG and AGEs. Moreover, EDYGA and DLLCIC were able to maintain the protein secondary structure and stabilize the band positions (amide I & II). Additionally, molecular simulations indicated that DLLCIC can spontaneously interact with the central site of BSA, specifically at Lys114 and Glu424 residues, through hydrogen bonds with an energy strength of −0.7 kcal/mol. Furthermore, CCK-8 and morphological experiments confirmed that EDYGA and DLLCIC improved cell survival against AGEs-induced cytotoxicity, with EC50 values of 17.64 μM for EDYGA and 15.08 μM for DLLCIC. These findings serve as a significant reference for the development of EDYGA and DLLCIC as effective antiglycation agents in the prevention of glycation-mediated diseases.